Formation of soil structure in long-term fertilised sandy soil: Role of the manganese oxides - Šimanský, Vladimir; Jonczak, Jerzy (Bulletin of Geography. Physical Geography Series, 2019)
We investigated the role of Mn oxides on the soil structure (contents of dry and water-stable aggregates) of sandy soil under a controlled long-term fertilisation experiment. We examined two experiments: a 94-year-term experiment with: no fertilisers, NPK fertilisers, and CaNPK fertilisers; and a 25-year-term experiment that included: farmyard manure and no mineral fertilisation, farmyard manure + NPK fertilisers, and Farmyard manure + CaNPK fertilisers. The results showed that in the 94-year-term trial, Mn oxides were increased in CaNPK treatment. In the 25-year-term experiment, the farmyard manure combined with NPK decreased total Mn and its oxides. In the 94-year-term experiment, the content of dry-sieved macro-aggregates (DSAma) and water-stable macro-aggregates (WSAma) increased due to fertilisation. The result of our study suggests that Mn oxides had positive effects mainly on higher size classes of DSAma and did not have any effect on water-stable aggregate contents.